Nuragic pottery from Hala Sultan Tekke: the cypriot-sardinian connection - Bürge, Teresa (Ägypten und Levante, 2019)
The present paper describes, for the first time, Cypriot evidence of Nuragic tableware from Sardinia discovered at Hala Sultan Tekke. This Late Bronze Age harbour and trade metropolis is situated near modern Larnaca on the southern littoral of Cyprus. The city’s exceptional wealth during the Late Bronze Age (1650–1050 BCE) was based on trade and cross-cultural connections with a vast area, including the entire Aegean, Anatolia, the Levant and Egypt. This is exemplified by the enormous amount of imported goods, most of which originated in the Mycenaean sphere of culture. Five handmade and burnished bowls of dark grey fabric with highly lustrous surfaces found at Hala Sultan Tekke were recently identified as imports from Sardinia. The main purpose of this article is to provide primary information about these exceptional finds and to place them in the context of trade between Sardinia and the eastern Mediterranean.